Empowering College Student Writers Through Collaboration - A. Chaedar Alwasilah (TEFLIN, 2001)
This study aimns at describing the effectiveness of collaborative writing as perceived by students of writing course at a university level. This study also aimns at describing the effectiveness of collaborative writing compared with the common practice of writing in high schools. Two groups of students were involved. They were asked to read an opinion article from newspaper published in Indonesia and to critique it in Indonesian. The results show that the respondents are likely to appreciate the experience of mutiple drafting. The students writing become not mere assigments, but the heart and soul of the entire term. As an implication of this study, it is suggested that the students be considered as apprentice writers filled with potential in the process of collaborative writing.